Antibiotic Profile for Bacteria Isolated from Urinary Tract Infection in Babylon Province - Hafedh, Zainab; Al-Isawi, Safaa A. (Central Asian Journal of Medical and Natural Science, 2025)
The purpose of this work was to ascertain the antibiotic profile of bacteria extracted from patient urinary tract infections (UTIs) from community urine samples. Commonly including bacterial and, occasionally, fungal or viral infections, urinary tract infections (UTIs) are healthcare concerns. Antibiotic resistance has grown out of the illogical prescribing and usage of antibiotics in UTI therapy. From male and female patients in several hospitals in Babylon province, Iraq, urine samples (152) were gathered with an age range of 1 to 80 years. In 67% of the samples—99/152—the research noted increase. Of the samples, 78% showed gram-negative bacteria; Gram-positive bacteria were recorded in 22%. Among women, the UTI prevalence was 73%; among men, it was 27%. The most prevalent uropathogenic bacteria were Escherichia coli ( 46%, 46/99), followed by, Staphylococcus aureus ( 25%, 25/99), Enterobacter cloacae ( 9, 9/99), Proteus mirabilis ( 6%, 6/99), Klebsiella pneumoniae (6%, 6/99) , Streptococcus (3%, 3/99) , Acinetobacter ( 2%, 2/99) Pseudomonas aeruginosa ( 1%, 1/99) , and serratia marcescence (1%, 1/99). Pseudomonas aeruginosa , serratia marcescence, Proteus mirabilis, Streptococcus and Acinetobacter as being sensitive to imipenem (100%) and Escherichia coli (93%), sensitive to cefepime(100%) serratia marcescence and Acinetobacter, sensitive to meropenem (100%) serratia marcescence and Streptococcus, sensitive to Amikacin (100%) Acinetobacter and Pseudomonas aeruginosa, sensitive to gentamicin(100%) serratia marcescence, Acinetobacter and Pseudomonas aeruginosa. sensitive to ciprofloxacin(100%) Streptococcus. sensitive to cefotaxime(100%) serratia marcescence . sensitive to levofloxacin(100%) serratia marcescence . and resistant to ceftazidime (100%) serratia marcescence , Acinetobacter , Streptococcus and Pseudomonas aeruginosa. resistant to cefepime (100%) Pseudomonas aeruginosa. resistant to meropenem (100%) Pseudomonas aeruginosa. resistant to Amikacin(100%) serratia marcescence and Streptococcus. resistant to gentamicin(100%) Streptococcus. resistant to ciprofloxacin (100%) serratia marcescence and Pseudomonas aeruginosa. resistant to Ampicillin/sulbactam (100%) serratia marcescence, Klebsiella pneumoniae Streptococcus, and Pseudomonas aeruginosa . resistant to cefotaxime(100%) Pseudomonas aeruginosa and resistant to levofloxacin (100%) Pseudomonas aeruginosa.